Blackness and La Francophonie : anti-Black racism, linguicism and the construction and negotiation of multiple minority identities - Madibbo, Amal I. (Collection langues officielles et sociétés., 2021)
This book uncovers intricate convergences and divergences among Blackness, Canadian-ness and La Francophonie, positing anti-Black racism, linguistic discrimination, slavery, and colonialism and neo-colonialism as sites of identity exclusion. However, Black agency reconstructs and renegotiates identity meanings and praxis to strengthen belongingness and pave the way for inclusion in the future.--